THE STRAIN OF MEGA EVENTS ON LOCAL RESOURCES: A CASE STUDY OF 2023 AFCON HOSTED BY COTE D'IVOIRE (American Journal of Research in Humanities and Social Sciences, 2025)
This paper investigated the strain of mega events on local resources: A case study of 2023 AFCON in Cote d'ivoire. The research design adopted for this study is descriptive and survey-based, which enabled the systematic collection of primary data through the administration of a structured questionnaire. The study focused on a sample of 150 respondents, selected from various communities within the Local Government Area. Descriptive analysis was employed to analysis the data. Result from the study revealed that hosting the AFCON competition will positively impact on Nigeria's economy. It will increase local tourism and cultural exchange in Nigeria. Hosting the AFCON competition will increase creation of job opportunities for the locals. It will promote peace and unity through sports amongst Nigerians. Result also showed that hosting the AFCON competition has more benefits than concerns on Nigerians and Nigeria.